Evaluating Effects of Public Speaking Training on Developing Communication Competence among Youths: A Field Study of Panauti Municipality-12, Kavrepalanchok (Punyawati Journal, 2026)
This study evaluates effects of public speaking training program conducted by Panauti Municipality ward no. 12. The training focused on empowering youths through building an effective communicative skill who are interested in future leadership and better professionalism. The study used quantitative approach and evaluation research method. Required data are collected from 25 youths (17 female and 8 male) who were thoughtfully participated in four days training program. The training participants were selected from four major settlements (Kalati, Bhumidanda, Chindu and Simpani) of the ward. For the evaluation, the study used Kirkpatricks Four-Level Training Evaluation Model. The study found noticeable and significant improvements in how participants rated their own communication skills, public speaking, and confidence levels. Besides, the training stressed ethical and respectful ways to communicate during public speaking. The higher level of participants’ satisfaction made the program more relevant. However, the satisfaction levels were differ due to sex group, marital status and occupational status of the participants. Females and unmarried ones reported bigger gains and more engagement compared to males or married people. That variation signifies because of social roles or what stage of life they are in. The training program becoming effective for school-going youths who were the dominant participants. The study concludes that locally designed participatory models of training resulted significant communication competencies among the youths. For wider impact of such training in the community, local government authorities need to organize such skill development training regularly and inclusively.